Residency and behavioural patterns of coastal bottlenose dolphins (Tursiops truncatus) in the Arrábida and Tróia shores (Portugal) - Martinho, Francisco Oliveira Martins Marques, 1987- (2012)
Tese de mestrado. Biologia (Biologia da Conservação). Universidade de Lisboa, Faculdade de Ciências, 2012